Reconstruction of Polopalo Pedagogy: Restoring the Values of Gorontalo Local Wisdom Amidst the Hegemony of Diatonic Music in Arts Education - Febriyando (SocioEdu: Sociological Education, 2026)
Art education in Gorontalo faces the phenomenon of sonic imperialism, which forces traditional Polopalo musical instruments to transform into a diatonic tone system for the sake of curriculum standardization and modernization. This transformation causes an erosion of sound identity, where the unique acoustic characteristics of bamboo are sacrificed in pursuit of Western standard frequency precision, resulting in the cultural alienation of students from their local heritage. This study aims to dissect the aesthetic and organological impacts of Polopalo diatonicization and formulate pedagogical reconstruction strategies capable of restoring local wisdom values. Using a qualitative approach with an ethnomusicological case study design, data was collected through in-depth interviews, participatory observation, and documentation studies of groups of maestros and education practitioners in Gorontalo. The results of the study show a fundamental epistemological shift, in which the terminology of local sound classification (Mo bulongo, Mo toliyongo, Mo elenggengo) has been replaced by a solmization system, creating a practice of cultural museumization in schools. The findings also confirm the phenomenon of timbral subordination or loss of richness in diatonic Polopalo when combined with modern instruments. However, this aesthetic degradation is not solely due to organological factors, but is exacerbated by a crisis of acoustic literacy and non-idiomatic orchestration techniques among composers. As a solution, this study recommends the application of the Musical Bilingualism model, which places mastery of traditional sound characteristics as the main aesthetic foundation before students explore diatonic variants, in order to preserve the continuity of Gorontalo's musical identity.